Remote Sensing and Geospatial Technologies for Coastal Ecosystem Assessment and Management - Yang, Xiaojun; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2009)
In this landmark publication, leading experts detail how remote sensing and related geospatial technologies can be used for coastal ecosystem assessment and management. This book is divided into three major parts. In the first part several conceptual and technical issues of applying remote sensing and geospatial technologies in the coastal environment are examined. The second part showcases some of the latest developments in the use of remote sensing and geospatial technologies when characterizing coastal waters, submerged aquatic vegetation, benthic habitats, shorelines, coastal wetlands and watersheds. Finally, the last part demonstrates a watershed-wide synthetic approach that links upstream stressors with downstream responses for integrated coastal ecosystem assessment and management.
Remote Sensing, Geospatial Technologies and Coastal Ecosystems -- Remote Sensing, Geospatial Technologies and Coastal Ecosystems -- Conceptual and Technical Issues -- Sensors and Techniques for Observing Coastal Ecosystems -- Geographic Information Systems and Spatial Analysis for Coastal Ecosystem Research and Management -- Fuzzy Approach for Integrated Coastal Zone Management -- Spatial Data Infrastructures for Coastal Environments -- Remote Sensing of Coastal Waters -- Airborne Remote Sensing of Chlorophyll in Chesapeake Bay, USA -- Bio-Optical Characteristics and Remote Sensing in the Mid Chesapeake Bay Through Integration of Observations and Radiative Transfer Closure -- Mapping Submerged Aquatic Vegetation and Benthic Habitats -- High-Resolution Ocean Color Remote Sensing of Coral Reefs and Associated Benthic Habitats -- An Integrated Approach to Benthic Habitat Mapping Using Remote Sensing and GIS: An Example from the Hawaiian Islands -- Assessment of the Abundance of Submersed Aquatic Vegetation (SAV) Communities in the Chesapeake Bay and its Use in SAV Management -- Distribution and Spatial Change of Hudson River Estuary Submerged Aquatic Vegetation: Implications for Coastal Management and Natural Resource Protection -- Mapping Marine Macrophytes along the Atlantic Coast of Tierra Del Fuego (Argentina) by Remote Sensing -- Shoreline Change, Coastal Wetland and Watershed Characterization -- Shoreline Mapping and Coastal Change Studies Using Remote Sensing Imagery and LIDAR Data -- Remote Sensing of Coastal Mangrove Forest -- Remote Sensing Support for Tidal Wetland Vegetation Research and Management -- Assessment of Coastal-Vegetation Habitats Using Airborne Laser Remote Sensing -- Measuring Habitat Changes in Barrier Island Marshes: An Example from Southeastern North Carolina, USA -- Mapping Fire Scars and Marsh Recovery with Remote Sensing Data -- Response of Reed Mudflats in the Caspian Coastal Zone to Sea Level Fluctuations -- Integrating Satellite Imagery and Geospatial Technologies for Coastal Landscape Pattern Characterization -- Integrated Coastal Ecosystem Assessment -- Remote Sensing and Spatial Analysis of Watershed and Estuarine Processes for Conservation Planning in Elkhorn Slough, Monterey County, California -- Runoff Water Quality, Landuse and Environmental Impacts on the Bellairs Fringing Reef, Barbados.
Keywords: Geography; Geographical information systems; Geoecology; Environmental geology; Geography; Geographical Information Systems/Cartography.; Geography, general; Geoecology/Natural Processes; Electronic books